Application of the Meta-Theoretical Approach in the Review of Islamic Management Books - Sadegh Hasani Moghadam; Rohollah Tavallaee; Gholam Reza Godarzi; Meysam Babaee (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In recent years, for various reasons, including the introduction of management in the West as an independent science and also due to the social needs of Islamic societies to use Islamic management in the management of society and organizations, some Islamic scholars have tried to write books on Islamic management. Authors try to write books which consider the presuppositions of various theories and in this regard, one of the valuable books in this field is the book "Islamic Management" which is our concern in this article. The present book focuses on different types of views on Islamic management as well as different trans-theoretical views on Islamic management. This book also deals with formal, theoretical, and content critique through the application of meta-theoretical technique and the method of content analysis of the book. Finally, it is suggested that technical and literary editing of the book are needed, more attention should be paid to the richness of the book content and the issue of task orientation would be discussed in the chapters related to planning, supervision, and control.